Structure, mechanical properties, and corrosion resistance of low-nickel nitrogen-alloyed austenite stainless steel - Muradian, Sarkis; Sun, Yan; Zhong, Qian; Su, Chen; Sun, Wenqiang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2026)
This study investigates the structure, mechanical properties, and corrosion resistance of low-nickel nitrogen-alloyed austenitic stainless steels (Cr17Mn9Ni3N, 05Cr18Mn10Ni3N) as cost-effective alternatives to conventional AISI 304L and AISI 321 grades. The alloys were produced by vacuum induction melting with nitrogen introduced via nitrided ferrochrome. Microstructural analysis confirmed fully austenitic structures with finer grain sizes (ASTM No. 4.5–6.0) compared to conventional steels (ASTM No. 3.5–4.0). Mechanical testing revealed superior yield strength (~414 MPa) and tensile strength (~730–748 MPa) in nitrogen-alloyed steels, attributed to solid-solution strengthening by nitrogen. However, the impact toughness at cryogenic temperatures (-196°C) was reduced, and brittle facets were found on the fracture surface. Potentiodynamic polarization tests showed that AISI 304L steel exhibited a higher pitting potential. The pitting potentials of Cr17Mn9Ni3N and 05Cr18Mn10Ni3N steels were lower than that of AISI 304L but higher than that of AISI 321 steel. Economic analysis highlighted significant cost savings potential through nickel substitution with nitrogen. The results validate nitrogen-alloyed steels as viable alternatives for applications requiring high strength and corrosion resistance, though cryogenic applications require careful nickel content optimization.
Keywords: low-nickel nitrogen-alloyed stainless steel; austenite stability; mechanical properties; corrosion, low-temperature toughness, cost-effectiveness